Predictors of Acceptance of Early Retirement Offers for Workers - Schell, Bernadette; Lebrasseur, Rolland; Renaud, Robert (Relations industrielles / Industrial Relations, 1989)
The purpose of this study was to investigate whether previously identified socio-demographic, psychographic, health state, financial state, and attitudinal variables could successfully discriminate blue-collar workers in the resource industries in Northern Ontario who accepted companies' retirement offers from those who rejected them. Such a discriminant function was developed and discussed. The «hit rate» was an impressive 76%.